Novel strategies to grow natural fibers with improved thermal stability and fire resistance. (20th October 2021) - Zhang, Xijin; Fan, Xudong; Han, Chanjuan; Li, Yanjun; Price, Erik; Wnek, Gary; Liao, Ya-Ting T.; Yu, Xiong (Bill)
Abstract: This study aims to produce natural grown fungi fiber with improved thermal stability and fire resistance. A novel strategy was explored by supplying nutrition enriched with silicon source. The results showed that Si enrichment improved the thermal stability of fungi fiber, possibly due to the thermally stable Si being utilized for fungi cell wall construction. Meanwhile, while nutrition enriched with low Si concentration accelerated fungi fibers production, further increases in Si concentration inhibited the fungal growth. These were attributed to the effects of Si and pH and on fungal metabolism, which was verified by Fourier Transform Infrared (FTIR) and Scanning Electron Microscope/Energy Dispersion Spectroscopy (SEM/EDS) microstructural characterization. Based on experimental observations, the study further investigated two strategies to facilitate fungi to utilize more Si in the fiber construction to enhance its fire resistance, i.e., application of pH buffer and selection of a new fungi strain with higher Si tolerance ( Fusarium oxysporum ). Both strategies achieved favorable results. Performance wise, fibers produced by both fungi Pleurotus ostreatus and Fusarium oxysporum featured higher residual weights than synthetic PVA fiber (by 2122% and 2223% respectively by Thermogravimetric Analysis (TGA)). Furthermore, with Si source enrichment, the fire resistance of fungi fibers improved further. For example, adding 3% Si to the nutrition of Fusarium oxysporum increased the TGA residual weight of its fiber by 93.81% compared with fiber grown without Si enrichment. Besides, Si enrichment reduced the peak heat release rate and the total heat of combustion of the produced fungi fiber by 50% and 35.09% respectively as measured by Microscale Combustion Calorimetry (MCC) test; these are also significantly less than those of the PVA fibers commonly used for building constructions (87.26% and 72.59% respectively), indicating improved fire resistance. Graphical abstract: Image 1